Developmental deficits of MGE-derived interneurons in the Cntnap2 knockout mouse model of autism spectrum disorder - Ahmed, Noorya Yasmin; Knowles, Rhys; Liu, Lixinyu; Yan, Yiming; Li, Xiaohan; Schumann, Ulrike; Wang, Yumeng; Sontani, Yovina; Reynolds, Nathan; Natoli, Riccardo; Wen, Jiayu; Del Pino, Isabel; et al. (Frontiers in Cell and Developmental Biology, 2023)
Interneurons are fundamental cells for maintaining the excitation-inhibition balance in the brain in health and disease. While interneurons have been shown to play a key role in the pathophysiology of autism spectrum disorder (ASD) in adult mice, little is known about how their maturation is altered in the developing striatum in ASD. Here, we aimed to track striatal developing interneurons and elucidate the molecular and physiological alterations in the Cntnap2 knockout mouse model. Using Stereo-seq and single-cell RNA sequencing data, we first characterized the pattern of expression of Cntnap2 in the adult brain and at embryonic stages in the medial ganglionic eminence (MGE), a transitory structure producing most cortical and striatal interneurons. We found that Cntnap2 is enriched in the striatum, compared to the cortex, particularly in the developing striatal cholinergic interneurons. We then revealed enhanced MGE-derived cell proliferation, followed by increased cell loss during the canonical window of developmental cell death in the Cntnap2 knockout mice. We uncovered specific cellular and molecular alterations in the developing Lhx6-expressing cholinergic interneurons of the striatum, which impacts interneuron firing properties during the first postnatal week. Overall, our work unveils some of the mechanisms underlying the shift in the developmental trajectory of striatal interneurons which greatly contribute to the ASD pathogenesis.